NOX4 Mediates Epithelial Cell Death in Hyperoxic Acute Lung Injury Through Mitochondrial Reactive Oxygen Species - Harijith, Anantha; Basa, Prathima; Ha, Alison; Thomas, Jaya; Jafri, Anjum; Fu, Panfeng; MacFarlane, Peter M.; Raffay, Thomas M.; Natarajan, Viswanathan; Sudhadevi, Tara (Frontiers in Pharmacology, 2022)
Management of acute respiratory distress involves O2 supplementation, which is lifesaving, but causes severe hyperoxic acute lung injury (HALI). NADPH oxidase (NOX) could be a major source of reactive oxygen species (ROS) in hyperoxia (HO). Epithelial cell death is a crucial step in the development of many lung diseases. Alveolar type II (AT2) cells are the metabolically active epithelial cells of alveoli that serve as a source of AT1 cells following lung injury. The aim of this study was to determine the possible role of AT2 epithelial cell NOX4 in epithelial cell death from HALI. Wild type (WT), Nox4fl/fl (control), and Nox4−/−Spc-Cre mice were exposed to room air (NO) or 95% O2 (HO) to investigate the structural and functional changes in the lung. C57BL/6J WT animals subjected to HO showed increased expression of lung NOX4 compared to NO. Significant HALI, increased bronchoalveolar lavage cell counts, increased protein levels, elevated proinflammatory cytokines and increased AT2 cell death seen in hyperoxic Nox4fl/fl control mice were attenuated in HO-exposed Nox4−/−Spc-Cre mice. HO-induced expression of NOX4 in MLE cells resulted in increased mitochondrial (mt) superoxide production and cell apoptosis, which was reduced in NOX4 siRNA silenced cells. This study demonstrates a novel role for epithelial cell NOX4 in accelerating lung epithelial cell apoptosis from HALI. Deletion of the Nox4 gene in AT2 cells or silencing NOX4 in lung epithelial cells protected the lungs from severe HALI with reduced apoptosis and decreased mt ROS production in HO. These results suggest NOX4 as a potential target for the treatment of HALI.